The satapur moonstone ebook - Massey, Sujata (Perveen Mistry, 2019)
The highly anticipated follow-up to the critically acclaimed novel The Widows of Malabar Hill . India, 1922: It is rainy season in the lush, remote Sahyadri mountains, where the princely state of Satapur is tucked away. A curse seems to have fallen upon Satapur’s royal family, whose maharaja died of a sudden illness shortly before his teenage son was struck down in a tragic hunting accident. The state is now ruled by an agent of the British Raj on behalf of Satapur’s two maharanis, the dowager queen and her daughter-in-law.   The royal ladies are in a dispute over the education of the young crown prince, and a lawyer’s counsel is required. However, the maharanis live in purdah and do not speak to men. Just one person can help them: Perveen Mistry, Bombay’s only female lawyer. Perveen is determined to bring peace to the royal house and make a sound recommendation for the young prince’s future, but she arrives to find that the Satapur palace is full of cold-blooded power plays and ancient vendettas. Too late, she realizes she has walked into a trap. But whose? And how can she protect the royal children from the palace’s deadly curse?